Spontaneous Remission of Primary Hyperparathyroidism Related to an Autoimmune Disease: A Case Report - Barbara C. Silva, MD, PhD; Jessica Fleischer, MD; Zachary Lenane, BS; Wen-Wei Fan, MPH; Donald J. McMahon, MS; John P. Bilezikian, MD (AACE Clinical Case Reports, 2015)
ABSTRACT: Objective: To report the unusual case of a woman with unequivocal primary hyperparathyroidism (PHPT) for 13 years who experienced spontaneous remission of her disease concomitant with the diagnosis of psoriatic arthritis.Methods: Clinical presentation, clinical course over 23 years of follow-up, and review of the pertinent literature are presented.Results: A 42-year-old woman was referred for evaluation of persistent hypercalcemia 2 months after unsuccessful parathyroid surgery for PHPT, in which a single, hyperplastic parathyroid gland was removed. Further evaluation confirmed persistent PHPT evidenced by hypercalcemia (12.1 mg/dL), elevated parathyroid hormone (PTH) level (118 pg/mL), normal calcium urinary excretion, and increased bone turnover markers. Persistent hypercalcemia and serum levels of PTH above normal were observed for 11 years after the parathyroid surgery. Thereafter, the patient experienced a downward trend and ultimate normalization of her serum calcium and PTH, which was associated, remarkably, with the development of psoriatic arthritis. Since return to normal of the serum calcium and PTH levels, the PHPT remission has persisted for 10 years without any signs of recurrent disease.Conclusion: Spontaneous remission of PHPT is exceedingly rare, and when it occurs, it is usually related to parathyroid hemorrhage or infarction. The patient's clinical course was not characteristic of parathyroid hemorrhage or infarction, and the concomitant appearance of psoriatic arthritis, an autoimmune disease, raises the possibility of an immune-mediated process explaining this outcome.Abbreviations: BMD bone mineral density CaSR calcium-sensing receptor NALP5 NACHT leucine-rich-repeat protein 5 NSAIDS nonsteroidal anti-inflammatory drugs PHPT primary hyperparathyroidism PTH parathyroid hormone